DISIPLIN PEGAWAI NEGERI SIPIL PADA DINAS PENDIDIKAN PEMUDA DAN OLAH RAGA KABUPATEN ROKAN HULU - Ratmi, Yanuriva; Rusli, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Discipline Civil servants In Department of Youth Education and Sports Rokan Hulu. The purpose of the study is to identify and analyze the Discipline of employees at the Department of Education, Youth and Sports if Rokan Hulu. Type of study is a qualitative method by using interviews and observation as a data collection tool to expose the employee discipline problems. The results showed that the enforcement of discipline in the field of education department secretariat on Youth and Sports Rokan Hulu District has not gone well in line with expectations visible from only a creation rules and sanction without a decrease in the level of disciplinary offenses, the growing number of employees who leave assignments during office hours . Factors that hinder enforcement of this discipline is a factor leadership, work environment, and ability. Keywords: Discipline, Civil Servant, Department of Youth Education and Sports